Vocational Students' Perspectives on Using Spotify for English Listening: Persepsi Siswa Kejuruan Terhadap Penggunaan Spotify untuk Mendengarkan Bahasa Inggris - Fiani, Alim Nuril; Taufiq , Wahyu (Indonesian Journal of Education Methods Development, 2024)
General Background: The role of technology in language education has gained increasing attention, particularly in the context of listening skills development among students. Specific Background: While various applications exist for language learning, limited research focuses on students' perceptions of using platforms like Spotify for enhancing their English listening abilities. Knowledge Gap: Existing literature lacks qualitative insights into how vocational high school students perceive and utilize Spotify as a tool for language acquisition. Aims: This study aims to explore the perceptions of Vocational High School (SMK) students regarding the use of Spotify to study English listening skills. Results: Employing a descriptive qualitative research design, data were collected from two informants from the X BD 2 class. Findings indicate that students view Spotify as a beneficial audio resource that aids in their English listening comprehension. Novelty: This research contributes new qualitative insights into the effectiveness of Spotify in language learning, emphasizing students' perspectives. Implications: The results suggest that integrating popular audio applications like Spotify can enhance students' engagement and support their English learning process, highlighting the potential for innovative teaching methods in vocational education. Highlights: Student Perceptions: Vocational students recognize Spotify as a valuable tool for improving English listening skills. Qualitative Insights: The study utilized descriptive qualitative methods to gather in-depth perspectives from participants. Supportive Resource: Spotify is identified as an effective audio application that enhances students' language learning experience. Keywords: Spotify, listening skills, vocational students, qualitative research, English learning.